Istanbul Chamber of Certified Public Accountants (ISMMMO) The Key Element of Accounting Profession - İlkim Mengülerek (Türk Kütüphaneciliği)
The purpose of this article is to indicate the identity struggle of a profession, the endeavors in the journey from Association to Chamber, the steps taken within this context, the achievements in a short period of time, the organizational development of Istanbul Chamber of Certified Public Accountants (ISMMMO) between 1990 and 2009, the social function of the Chamber and its contributions to the profession in terms of information and science. The Information Access Center (IAC), established in 2006, serves not only in Istanbul but all over Turkey. IAC collects all books and periodicals in the field of accountancy published in Turkey and tracks certain foreign publications. It also continues to improve its services with the accountancy bibliography (books, articles), daily newsletter, index of "Mali Çözüm (Finance Solutions)" magazine, and through activies and studies in the Library Week.